The role of feeedback in improving writing skill - Putri Fadillah Batubara; Wika Arta Mefia; Ahmad Rizki Ardi Pratama (Jurnal Multidisiplin Dehasen (MUDE), 2023)
Helping students improve the quality of learning is one of the important goals of feedback in the teaching and learning process, especially in writing activities. In this literature study, the aim was to examine how teachers can provide effective feedback in writing classes. To achieve this, several expert opinions and previous research on feedback for writing skills have been collected and compiled into several strategies that can be used by teachers to provide effective feedback in writing activities. From this study, it was found that effective feedback from teachers can help students identify their level of proficiency and weaknesses in writing. By considering students' writing needs and goals, the feedback provided can help students evaluate their own achievements and correct weaknesses to improve their writing skills. Teachers can choose certain types of feedback based on the purpose of the writing and the needs of the students. Therefore, it is expected that the teacher can provide effective feedback to increase students' motivation in improving their writing skills. Furthermore, further research is expected to provide information about oral and written feedback in writing activities.